Developing Education Media of Health Protocol utilizing Live Coloring using Augmented Reality Technology - Akbar Permana Putra; Priyanto Priyanto (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
The objective of the present study is to produce a learning media product of health protocol implementation to children entitled "Awas Ada Virus Corona". This media utilized RD method and took several steps, namely preliminary research and data collection, research planning, product development, expert validation, product revision and final product. Feasibility testing is carried out by media experts by examining the multimedia construction domain consist of 3 aspects, namely guidance and information, program performance as well as systematic, aesthetic, and design aspects. Furthermore, a filled questionnaire by media experts was used to collect the data needed. Meanwhile, the descriptive statistic was used to analyzed the data gathered. The result of the present study is an application that can be used by children entitled " Awas Ada Virus Corona " as an educational media in implementing 3M of health protocol, namely wearing masks, washing hands, and maintaining a safe distance. The addition of Augmented reality technology with a live coloring feature is added in this application in reading markers to increase children's attractiveness. This augmented reality technology is applied in order to avoid the children only focus on gadgets, so children feel happy in using the familiar media and still interacting with the environment.